Graf Fuzzy Produk - Firmansyah, Fery; Bayu, Surarso (MATEMATIKA, 2011)
Fuzzy graph is a graph which is consists of a pairs of vertex and edge that have degree contained on closed interval of real number [0,1] on each edge and vertex. Product fuzzy graph was defined by Dr. V. Ramaswamy and Poornima B by replacing â€œinfimumâ€ in definition of fuzzy graph by â€œproductâ€. In this paper we study product fuzzy graph complete, in connection Â complement of produk fuzzy graph, join of produk fuzzy graph and multiplication of produk fuzzy graph. We show that complement of the multiplication of two product fuzzy graphs complete is a multiplication of its complement, in which this disposition produces nil graph. Â